Association between halitosis and female fecundability in China: a prospective cohort study - Xiaona Huo; Lin Zhang; Rong Huang; Jiangfeng Ye; Yulin Yang; Hao Zhang; Jun Zhang (BMC, 2021)
Abstract Background Periodontal diseases and poor oral hygiene are potentially associated with decreased female fecundability. Fecundability refers to the probability of conception during a given period measured in months or menstrual cycles. This study aims to examine whether halitosis is associated with female fecundability in a large sample of Chinese women who planned to be pregnant. Methods In 2012, a total of 6319 couples came for preconception care in eight districts in Shanghai, China and were followed by telephone contact. Three thousand nine hundred fifteen women who continued trying to be pregnant for up to 24 months remained for final statistical analyses. Halitosis was self-reported at the preconception care visit. Time to pregnancy (TTP) was reported in months and was censored at 24 months. Fecundability ratio (FR) was defined as the ratio of probability of conception among those with and without halitosis. FR and 95% confidence interval (CI) were estimated using the discrete-time Cox model. Results 80.1 and 86.1% of women had self-reported clinically confirmed pregnancy within 12 and 24 months, respectively. Halitosis was reported in 8.7% of the women. After controlling for potential confounders, halitosis was associated with a reduced probability of spontaneous conception (for an observation period of 12 months: adjusted FR 0.82, 95% CI 0.72-0.94; for an observation period of 24 months: adjusted FR 0.84, 95% CI 0.74-0.96). Conclusions Halitosis is associated with reduced fecundability in Chinese women.